1982
DOI: 10.1113/jphysiol.1982.sp014352
|View full text |Cite
|
Sign up to set email alerts
|

Reflex response of the rabbit hind‐limb muscle vascular bed to baroreceptor stimulation and its modification by pregnancy.

Abstract: SUMMARY1. The pressure-flow relationship of the blood-perfused skinned hind limb has been compared in primigravid pregnant and virgin non-pregnant rabbits while pressure within the vascularly isolated carotid sinus was held at a series ofnon-pulsatile values.2. At each level of sinus pressure the slope of the pressure-flow relationship was steeper in the pregnant animals. Thus, at all but the very lowest flows, the same flow was achieved at a lower perfusion pressure in the pregnant rabbits.3. When hind-limb v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Carotid sinus baroreflex depressor responses were equivalent, but pressor responses were attenuated in pregnant compared to nonpregnant animals. Subsequent studies revealed that this was due to attenuated increases in vascular resistance in nonuterine circulatory beds,9 rather than to attenuated changes in cardiac output10 during baroreceptor unloading (low carotid sinus pressure) in pregnant animals. Although these data suggest that autonomic neural mechanisms may be involved, interpretation of the results is complicated by the fact that vascular responsiveness to circulating and neurally released vasoconstrictors is decreased in pregnancy 11–13…”
Section: Effects Of Pregnancy On Arterial Baroreflex Functionmentioning
confidence: 99%
“…Carotid sinus baroreflex depressor responses were equivalent, but pressor responses were attenuated in pregnant compared to nonpregnant animals. Subsequent studies revealed that this was due to attenuated increases in vascular resistance in nonuterine circulatory beds,9 rather than to attenuated changes in cardiac output10 during baroreceptor unloading (low carotid sinus pressure) in pregnant animals. Although these data suggest that autonomic neural mechanisms may be involved, interpretation of the results is complicated by the fact that vascular responsiveness to circulating and neurally released vasoconstrictors is decreased in pregnancy 11–13…”
Section: Effects Of Pregnancy On Arterial Baroreflex Functionmentioning
confidence: 99%
“…Details of the recordingprocedures and the measurement ofblood gases have been given (Humphreys & Joels, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…1). The arterial inflow to the left hind limb was vascularly isolated and the limb perfused as described in the preceding paper (Humphreys & Joels, 1982) with the exception that the perfusion pump was supplied with blood from the left common carotid artery. Two series of experiments were performed: in one the skin of the perfused hind limb remained in situ; in the other the limb was skinned as previously described to restrict the circulation largely to muscle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further details of the perfusion and the various checks for completeness of vascular isolation have been given previously (Humphreys & Joels, 1982a …”
Section: Preparation Of 8inu8 Aortic and Lumbar Sympathetic Nervesmentioning
confidence: 99%